DENTAL IMPLANTS AS AN OPTION FOR MISSING TOOTH/TEETH REPLACEMENT: A STUDY ON PATIENT AWARENESS AND SOURCES OF INFORMATION - MISHRA, AMBRISH; TIWARI, RAJNARAYAN; TRIPATHI, GEETA MISHRA; SHARMA, DIVASHREE (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: This study was designed with an aim to assess the level of awareness regarding dental implant as a treatment modality for the replacement of missing teeth in the patients reporting to dental outpatient department and to determine their sources of information regarding implants. Methods: This was a questionnaire-based study to assess the awareness about dental implants and the related sources of information in 350 patients who reported to Department of Dentistry, Shyam Shah Medical College Rewa, Madhya Pradesh from 1st October 2022 to 31st December 2022. Results: Only 36.86% (n=129) of participants had heard of dental implants. Among these patients (N=129), only 30.23 % (n=39) received information about dental implants from dentists. Only 4 (3.10%) patients had themselves undergone treatment with dental implants. Awareness regarding implant composition was poor with only 6.98% (n=9) participants being aware that implants are made of titanium. Fear of surgery (33.33%) and high treatment cost (30.23%) were the most common limiting factors that governed the decision of patients regarding undergoing treatment with dental implants. Conclusion: The findings of the study indicate a low level of awareness about dental implants as a treatment option for replacing missing teeth. A very less number of participants received information from reliable sources. It is important to create awareness in general population regarding feasibility of implants for prosthetic rehabilitation and to make implant treatment easily accessible and affordable.